Development and analysis of filament holder for fused filament fabrication 3D printer using Python programming language - Novak, Dmytro; Osaulenko, Sergey (Technologies and Engineering, 2025)
The work aimed to analyse and develop a 3D printer coil holder using the Python programming language. The methodology included a coil holder designed using computer-aided design (CAD) software, namely Autodesk Fusion 360. External libraries and plug-ins such as Stress Analysis and Generative Design were used for optimisation. The suitability of the developed design for improving the feeding of strings and reducing their tangling when printing on a 3D printer was determined. The operation of the coil holder with different types and coil sizes was analysed. The developed spool holder successfully passed 97% of the tests for printing models using PLA, ABS and PETG. Testing the measurements of the coil holder with a PROTESTER WDF-30 digital dynamometer revealed several essential observations: Teflon tubing added additional friction, increasing both the minimum and maximum forces by approximately 0.2 N, and slightly reducing the range between the minimum and maximum values; plastic coils showed lower minimum forces, 0.4 N, due to reduced friction, but a more extensive range, 0.5 N, due to their greater mass, and cardboard coils had higher minimum forces, 0.5 N, but a smaller range, 0.3 N; no tension significantly reduced both minimum, 0.2 N, and maximum, 0.3 N, forces, as well as the range between them, 0.1 N, and this condition increased the risk of coil entanglement; the effect of the Teflon tube was more pronounced under proper tension conditions, approximately 0.2-0.3 N; the high-tension setup showed significantly higher minimum, 0.8 N, and maximum, 1.1 N, forces compared to the developed holder (minimum 0.5 N, maximum 0.8 N), but the range of acceptable values was similar, the increased minimum force in the high-tension setup could potentially lead to insufficient extrusion and increased extruder wear. The developed coil holder reduces the printer’s extruder mechanism load by maintaining an optimal tension in the range of 0.5 to 0.8 N. This can significantly extend the life of critical components, reducing the cost of maintaining the 3D printer